2021
DOI: 10.1111/irv.12901
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based assessment of risks for severe COVID‐19 disease outcomes

Abstract: Among approximately 4.6 million members of Kaiser Permanente Northern California, we examined associations of severe COVID‐19 with demographic factors and comorbidities. As of July 23, 2021, 16 182 had been hospitalized, 2416 admitted to an ICU, and 1525 died due to COVID‐19. Age was strongly associated with hospitalization, ICU admission, and death. Black persons and Hispanic ethnicity had higher risk of death compared with Whites. Among the comorbidities examined, Alzheimer's disease was associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
2
19
1
Order By: Relevance
“…After evaluating and assessing as much as 257 potential studies, 201 studies were removed due to outcome of interest being not available. In the end, what underlay this meta-analysis were eligible fifty-six articles with 426,261 COVID-19 patients [5] , [6] , [7] , [8] , [9] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] . The detail of selection process is shown by a chart flow in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After evaluating and assessing as much as 257 potential studies, 201 studies were removed due to outcome of interest being not available. In the end, what underlay this meta-analysis were eligible fifty-six articles with 426,261 COVID-19 patients [5] , [6] , [7] , [8] , [9] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] . The detail of selection process is shown by a chart flow in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, those urged us to investigate the association between asthma and COVID-19 mortality in a specific country or region. To date, a number of individual studies have explored the association between asthma and COVID-19 mortality in the United States with conflicting results [5] , [6] , [7] , [8] , [9] , but no quantitative meta-analysis on this topic was conducted to address this issue. Therefore, we performed a quantitative meta-analysis to investigate the impact of asthma on the risk for COVID-19 mortality in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic in the U.S. has disproportionately impacted communities of color with substantially higher rates of infection, hospitalization, and death documented in Asian, Black, and Hispanic people compared to White people ( 1 ). In addition, the pandemic has exacerbated deep-seated social and economic disparities related to living conditions and work environments ( 2 ) putting communities of color at heightened risk of COVID-19-related stressors and adverse mental heath outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated factors associated with severe COVID-19 outcomes that can be either environmental, population based, or genetic. For instance, a geographic and population variation in the disease course and outcome has demonstrated that individuals representing Black, Hispanic, or Asian ethnicities have a higher risk of death compared to Caucasians [ 2 , 3 ]. The identified risk factors of COVID-19 infection are advanced age, male sex, and comorbidities (especially: renal disease, oncological pathologies, chronic respiratory disease, and cardiovascular disease—excluding hypertension and dementia), but they do not fully explain the wide spectrum of disease manifestations [ 2 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a geographic and population variation in the disease course and outcome has demonstrated that individuals representing Black, Hispanic, or Asian ethnicities have a higher risk of death compared to Caucasians [ 2 , 3 ]. The identified risk factors of COVID-19 infection are advanced age, male sex, and comorbidities (especially: renal disease, oncological pathologies, chronic respiratory disease, and cardiovascular disease—excluding hypertension and dementia), but they do not fully explain the wide spectrum of disease manifestations [ 2 , 4 , 5 , 6 ]. Moreover, the viral load can play a role in the COVID-19 severity, as demonstrated for mortality, especially in combination with advanced age [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%